Surface Plasmon Resonance Assay for Label‐Free and Selective Detection of Xylella Fastidiosa. Issue 10 (28th July 2021) - Sarcina, Lucia; Macchia, Eleonora; Loconsole, Giuliana; D'Attoma, Giusy; Saldarelli, Pasquale; Elicio, Vito; Palazzo, Gerardo; Torsi, Luisa
Abstract : Xylella fastidiosa is among the most dangerous plant bacteria worldwide causing a variety of diseases, with huge economic impact on agriculture and environment. A surveillance tool, ensuring the highest possible sensitivity enabling the early detection of X. fastidiosa outbreaks, would be of paramount importance. So far, a variety of plant pathogen biomarkers are studied by means of surface plasmon resonance (SPR). Herein, multiparameter SPR (MP‐SPR) is used for the first time to develop a reliable and label‐free detection method for X. fastidiosa . The real‐time monitoring of the bioaffinity reactions is provided as well. Selectivity is guaranteed by biofunctionalizing the gold transducing interface with polyclonal antibodies for X. fastidiosa and it is assessed by means of a negative control experiment involving the nonbinding Paraburkholderia phytofirmans bacterium strain PsJN. Limit of detection of 10 5 CFU mL −1 is achieved by transducing the direct interaction between the bacterium and its affinity antibody. Moreover, the binding affinity between polyclonal antibodies and X. fastidiosa bacteria is also evaluated, returning an affinity constant of 3.5 × 10 7 m −1, comparable with those given in the literature for bacteria detection against affinity antibodies. Abstract : The screening of Xylella fastidiosa plant pathogen is performed by means of surface plasmon resonance. The study demonstrates the bacterium direct assay, performed on a gold surface modified with the anti‐ X. fastidiosa, covalently bound to the detecting interface. Unprecedent selectivity is shown by assaying the Burkholderia phytofirmans nonbinding bacterium. The affinity constant of the X. fastidiosa immunoassay is determined too.